Impact of Different Pollutant Sources on Human Health Using Solid Aerosol’s Elemental Analysis - Muhammad Attique Khan Shahid,; Khadim Hussain ,; Ahmad Raza, (Journal of Basic & Applied Sciences, 2013)
Atomic absorption spectroscopy (AAS) was used in this study to find out the metal constituents and concentration for Seven (7) trace metals in the atmosphere of Faisalabad. The maximum elemental constituents and concentration for Zn, Cu, Cr, Ni, Pb, Mg and Cd in ppm were found to be Cadmium Cd(1) in amounts ranging between (2.596→1.95475) in Pool (5→3), Chromium Cr(2) in amounts ranging between (0.0145→0.01125) in Pool (2→3), Nickel Ni(3) in amounts ranging between (0.9925→0.35575) in Pool (5→3), Lead Pb(4) in amounts ranging between (1.33675→0.2632) in Pool (2→3), Zinc Zn(5) in amounts ranging between (2.515→1.38825) in Pool (4→5), Magnesium Mg(6) in amounts ranging between (1.22125→1.15875) in Pool (4→5), Calcium Ca(7) in amounts ranging between (11.46725→3.53875) in Pool (4→3) respectively. Following pool wise trend pattern of identified elements in solid aerosols is given in Table 1 & 2. The comparison of results reported in literature with the obtained results showed some differences in concentrations which could be explained on the basis of climatological and meteorological set up of different pools under investigations. Furthermore, the health hazards due to identified trace metals were also investigated and were found that the metals were highly toxic and generating serious health hazards.